2008
DOI: 10.1016/j.thromres.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanism for recruitment and migration of CD133 positive cells to areas of vascular inflammation

Abstract: CD133+ cells can be utilized as a mast cell precursor population. The transendothelial migration is facilitated by the presence of tryptase and may utilize the PAF/PTAFR interaction in a manner similar to that involved in neutrophil transmigration. Following transmigration, a subset of these progenitor cells may mature into mast cells in the subendothelial space and play a role in propagation of the inflammatory process in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…CD68 is expressed on monocytes, and consequently tissue macrophages, and is therefore a reliable marker of atherosclerotic disease. Treatments for atherosclerosis define its benefits by, among other things, reducing the number of CD68 + cells derived from monocytes in the atherosclerotic plaque (Rastogi et al 2008). Our studies demonstrated marking to CD68 in the AT 21 days group on endothelial cells as well as a characteristic monocyte migration to a possible internal region of the arterial wall.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…CD68 is expressed on monocytes, and consequently tissue macrophages, and is therefore a reliable marker of atherosclerotic disease. Treatments for atherosclerosis define its benefits by, among other things, reducing the number of CD68 + cells derived from monocytes in the atherosclerotic plaque (Rastogi et al 2008). Our studies demonstrated marking to CD68 in the AT 21 days group on endothelial cells as well as a characteristic monocyte migration to a possible internal region of the arterial wall.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, CD133 is a marker of tumor cells that initiate a number of human neoplastic tumors, and therefore it may be possible to develop a marker in future therapies for cancer cells (Mizrak et al 2008). Following transmigration of these hematopoietic stem cells, a subset of progenitor cells can mature in the subendothelial space, and mast cells play a role in propagating the inflammation in atherosclerosis (Rastogi et al 2008). Our studies demonstrate marking CD133 on endothelial region of the aorta in AT 14 days group.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated previously that CD133+ cells, a mast cell precursor population, utilizes the PAF–PAFR interaction in a manner similar to that involved in PMN transendothelial migration (Rastogi et al. ). Therefore, we propose that increased endothelial cell PAF production in smokers may result in increased recruitment and accumulation of mast cells in the bladder wall.…”
Section: Discussionmentioning
confidence: 96%
“…; Rastogi et al. ). Generation of endothelial cell PAF is initiated by calcium‐independent phospholipase A 2 β (iPLA 2 β ) activation, which hydrolyzes the sn ‐2 fatty acid from membrane phospholipids, yielding a free fatty acid and lysophospholipid.…”
Section: Introductionmentioning
confidence: 97%
“…Second, when PAF-receptor knockout mice were exposed to UV radiation, no suppression of DTH or CHS was observed [137, 138]. Third, PAF is known to regulate the migration of many cell types, including tumor cells, neutrophils and leukocytes as well as mast cells [139144], and mast cells are known to express the PAF receptor and are able to respond to PAF [145]. Chacón-Salinas and colleagues confirmed that mast cell-deficient mice were resistant to the suppressive effect of UV-irradiation, and suppression of the CHS reaction was restored by reconstituting mast cell-deficient mice with normal bone marrow-derived mast cells.…”
Section: Paf and Uv-induced Immune Suppressionmentioning
confidence: 99%